A protracted outbreak of difficult-to-treat resistant Pseudomonas aeruginosa in a haematology unit: a matched case–control study demonstrating increased risk with use of fluoroquinolone. (February 2023) - Rice, W.; Martin, J.; Hodgkin, M.; Carter, J.; Barrasa, A.; Sweeting, K.; Johnson, R.; Best, E.; Nahl, J.; Denton, M.; Hughes, G.J.
Summary: Background: Between September 2016 and November 2020, 17 cases of difficult-to-treat resistant Pseudomonas aeruginosa (DTR-PA) were reported in haematology patients at a tertiary referral hospital in the North of England. Aim: A retrospective case–control study was conducted to investigate the association between DTR-PA infection and clinical interventions, patient movement, antimicrobial use and comorbidities. Methods: Cases were patients colonized or infected with the outbreak strain of DTR-PA who had been admitted to hospital prior to their positive specimen. Exposures were extracted from medical records, and cases were compared with controls using conditional logistic regression. Environmental and microbiological investigations were also conducted. Findings: Seventeen cases and 51 controls were included. The final model included age [>65 years, adjusted OR (aOR) 6.85, P =0.232], sex (aOR 0.60, P =0.688), admission under the transplant team (aOR 14.27, P =0.43) and use of ciprofloxacin (aOR 102.13, P =0.030). Investigations did not indicate case-to-case transmission or a point source, although a common environmental source was highly likely. Conclusion: This study found that the use of fluoroquinolones is an independent risk factor for DTR-PA in haematology patients. Antimicrobial stewardship and review of fluoroquinolone prophylaxis should be considered as part of PA outbreak investigations in addition to standard infection control interventions.